2012
DOI: 10.4070/kcj.2012.42.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Percutaneous Transcatheter Implantation of Pulmonary Arterial Stent in Congenital Heart Disease

Abstract: Background and ObjectivesPulmonary arterial stenosis is a relatively common complication after corrective operation of congenital heart disease. Unilateral stenosis of pulmonary arteries could result in decrease perfusion of affected lung, pulmonary regurgitation, or elevation of right ventricular pressure. Eventually there are increasing risks of right ventricular failure, arrhythmia, or sudden death. However we have limited data of pulmonary arterial stent in paediatric population as the treatment of branch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This might be explained by the increase in blood vessel diameter and is substantiated by studies that show the effectiveness of interventions for branch pulmonary artery stenosis on dilating the blood vessel. [15][16][17] Fogelman et al found no significant improvement for right pulmonary artery flow after the percutaneous intervention, which might be a result of the small sample size (n = 4). Overall, there is a general trend towards improved lung perfusion after a percutaneous intervention in the & p-value between lung perfusion post intervention and follow-up (both 6 months and 1 year) not significant (p > 0.05).…”
Section: Lung Perfusionmentioning
confidence: 94%
See 1 more Smart Citation
“…This might be explained by the increase in blood vessel diameter and is substantiated by studies that show the effectiveness of interventions for branch pulmonary artery stenosis on dilating the blood vessel. [15][16][17] Fogelman et al found no significant improvement for right pulmonary artery flow after the percutaneous intervention, which might be a result of the small sample size (n = 4). Overall, there is a general trend towards improved lung perfusion after a percutaneous intervention in the & p-value between lung perfusion post intervention and follow-up (both 6 months and 1 year) not significant (p > 0.05).…”
Section: Lung Perfusionmentioning
confidence: 94%
“…Percutaneous balloon angioplasty and stent implantation in branch pulmonary artery stenosis have been proven safe and effective in patients with CHD. [15][16][17] However, the (long-term) outcomes on exercise capacity, right ventricular function, and lung perfusion remain fairly unknown. Therefore, the aim of this review was to describe the (longterm) effects of percutaneous branch pulmonary artery interventions on exercise capacity, right ventricular function, and lung perfusion in biventricular CHD.…”
mentioning
confidence: 99%
“…However, in Korea, only a few reports about stent implantation in patients with CHD have been published, and they included only immediate or short-term follow-up in patients with PAS. 4 5) The purpose of this study was to evaluate the safety and efficacy of intravascular stent implantation in various types of CHD, and to assess the improvement in immediate and midterm outcomes based on our experience in a single institute.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Korean Circulation Journal, Ko et al 1) report on the effectiveness and safety of percutaneous implantation of pulmonary arterial stents in congenital heart disease between 1999 and 2010 in one institute. Since Dr. Mullins recognized the potential for stents to treat pulmonary arterial stenosis effectively which were compared to the surgical methods, many reports about these experiences have been reported.…”
mentioning
confidence: 99%
“…Most of the studies demonstrated the effectiveness of pulmonary arterial stenting by increasing pulmonary artery size, reducing pressure gradients, decreasing right ventricular pressure and improving the disparity in pulmonary arterial blood flow. 2 - 5) However, there are few reports with long-term follow-up data in a large population of patients, especially no multicenter, randomized controlled studies as Ko et al 1) noted. Therefore, in spite of the efforts of many doctors, the use of stents to treat pulmonary arterial stenosis is still considered "off label"-i.e., not approved by the Food and Drug Administration, even though the investigational device exemption (IDE) was obtained by Dr. Mullins' efforts.…”
mentioning
confidence: 99%